2012
DOI: 10.1038/ijo.2011.272
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of lifestyle interventions to treat overweight or obesity in children

Abstract: OBJECTIVE:To estimate lifetime cost effectiveness of lifestyle interventions to treat overweight and obese children, from the UK National Health Service perspective. DESIGN: An adaptation of the National Heart Forum economic model to predict lifetime health service costs and outcomes of lifestyle interventions on obesity-related diseases. SETTING: Hospital or community-based weight-management programmes. POPULATION: Hypothetical cohorts of overweight or obese children based on body mass data from the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 37 publications
3
60
0
2
Order By: Relevance
“…Although more modest, significant improvements in weight and associated medical outcomes can still be made in adolescents, although additional research is warranted with this age group. Research also suggests that lifestyle interventions are probably cost-effective, although cost savings and health benefits may not be notable until the sixth or seventh decade of life (Hollingworth et al, 2012), with family-based treatment more cost-effective than treating parents and children separately . Additional research is needed to evaluate a stepped-care approach to treatment and further enhance the potency of treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Although more modest, significant improvements in weight and associated medical outcomes can still be made in adolescents, although additional research is warranted with this age group. Research also suggests that lifestyle interventions are probably cost-effective, although cost savings and health benefits may not be notable until the sixth or seventh decade of life (Hollingworth et al, 2012), with family-based treatment more cost-effective than treating parents and children separately . Additional research is needed to evaluate a stepped-care approach to treatment and further enhance the potency of treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the studies [64][65][66][67][68][69][70][71][72] were published in 2012 or later, and of note in the current report is that the initial searching of the literature in 2012 was used as the basis for the conceptual modelling framework for HeLP, as set out below, and it was, therefore, based on a limited literature (as described below and in Table 26). However, a number of the more recent studies adopt the methodological framework used in the earlier literature, which has influenced the conceptual framework used for the HeLP-specific research.…”
Section: Resultsmentioning
confidence: 99%
“…Two models were identified. 62,63 Five models (reported in nine publications) were subsequently identified that were published between 2012 and 2015, [64][65][66][67]69 with the majority of these published in the last 2 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations